El Rincón InterCreativo. Número 74 - Malaspina, Uldarico; Sandoval Quispe, Renzo; Alva Montañez, Fernando Alejandro; Landa Chávez, Gonzalo; Reyes Parra, Guillermo (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2025)
Comentarios al problema del número anterior.